2019
DOI: 10.2134/jeq2019.01.0007
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Database to Collect Emission Values for Livestock Systems

Abstract: Growing demand for animal products has contributed to an increase in biogeochemical fluxes, leading particularly to gaseous ammonia, methane, and nitrous oxide emissions into the atmosphere. Developing accurate knowledge on the sources and magnitude of gas emissions from the livestock sector is essential to reducing emissions, while meeting other societal expectations, and to implementing effective regulations. To this end, a database called ELFE (ELevage et Facteurs d'Emission; i.e., Livestock and Emission Fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 16 publications
0
20
2
Order By: Relevance
“…et al, 2018), ELFE (Vigan et al, 2019), and the 2019 refinement of the 2006 IPCC guidelines (IPCC, 2019). The U.K. studies (Chadwick et al, 2018;Thorman et al, 2020) can be found in the archived data sources of the United Kingdom's Agricultural and Environmental Data Archive (AEDA, 2019), where all relevant N 2 O and NH 3 studies on excreta and manure (27 studies in total) were included in DATAMAN.…”
Section: Core Ideasmentioning
confidence: 99%
See 4 more Smart Citations
“…et al, 2018), ELFE (Vigan et al, 2019), and the 2019 refinement of the 2006 IPCC guidelines (IPCC, 2019). The U.K. studies (Chadwick et al, 2018;Thorman et al, 2020) can be found in the archived data sources of the United Kingdom's Agricultural and Environmental Data Archive (AEDA, 2019), where all relevant N 2 O and NH 3 studies on excreta and manure (27 studies in total) were included in DATAMAN.…”
Section: Core Ideasmentioning
confidence: 99%
“…Selection criteria for NH 3 emission studies were: (a) the studies were field based; (b) the NH 3 emissions were measured using micrometeorological methods, aspirated F I G U R E 1 Summary of process for collating data of DATAMAN database and the focus of the current paper. AEDA, Agricultural and Environmental Data Archive (AEDA, 2020); ALFAM2, Ammonia Loss from Field-Applied Manure (Hafner et al, 2018); ELFE, ELevage et Facteurs d'Emission (Vigan et al, 2019) chambers, wind tunnels, or passive sampling techniques; (c) the measurements were conducted for at least 1 d for all manures (except for poultry) and for 7 d or more for poultry manure experiments (due to the slow rate of urea hydrolysis of uric acid present in poultry manure); (d) cumulative NH 3 emissions or EF values were reported; (e) the N treatments were limited to one N source; and (f) activity data on N load were available or could be calculated from information provided. As for N 2 O, a subsequent study will determine the influence of experiment duration on revised NH 3 EF values.…”
Section: Core Ideasmentioning
confidence: 99%
See 3 more Smart Citations